MANFAAT PEMBERIAN JUS BUAH NAGA UNTUK PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL DENGAN ANEMIA DI KLINIK ZAHIRA PURWAKARTA TAHUN 2021 - Desi Trisiani (Fakultas Ilmu Kesehatan Unsika, 2021)
Anemia is a condition in which red blood cells (erythrocytes ) decrease or decrease in hemoglobin, so that the oxygen-carrying capacity for the organ needs in the mother and fetus is reduced. The purpose of this study was to determine the effect of dragon fruit juice on increasing hemoglobin levels in pregnant women with anemia. The design of this study is an experimental study with a one grup pre test-post test. Design approach with a population of 43 pregnant women with anemia, sampels were taken using the total sampiling technique. The independent variable in this study was the administration of dragon fruit juice. The dependent variable was the change in HB levels in pregnant women with anemia. Collecting data using primary data using observation sheets measuring HB levels before and after examination. Research analysis using t-test. The results showed that the mother’s Hb level before consuming drahon fruit juice was obtained Mean 9.28 gr/dl, Median 9.50 gr/dl, mode 10 gr/dl and SD 7.7 gr/dl. Mother’s Hb level after consuming dragon fruit juice obtained Mean 10.4 gr/dl, Median 10.6 gr/dl, Mode 11 gr/dl and SD 8 gr/dl. The results of the t-tes with a significance level α=0,05 obtained p_value = 0,000 (p_value < α (0,05)) so it was concluded thet there was an effect of giving dragon fruit juice on increasing Hb levels of pregnant women. Keyword : Dragon Fruit Juice, Anemia, Pregnant Women